Comparing outcomes of group and individualized physiotherapy treatment models for children with cerebral palsy in Ghana: a quasi-experimental study - Banini, Sandra (Division of Physiotherapy, 2024)
Background: Cerebral palsy (CP) is a global concern. The primary caregivers of children living with CP play a vital role in influencing the nature and direction of care the children receive. Physiotherapists are rehabilitation specialists who assist in efficient motor movement and quality of life in children with CP. Therefore, effective and appropriate physiotherapy treatment is essential to meeting the needs of both caregivers and children. The study compared the individual (IPTM) and group physiotherapy treatment models (GPTM) at two teaching hospitals in Ghana using the quasi-experimental design. Methods: Forty (n = 40) children with spastic cerebral palsy (SCP) took part in the study, along with their respective caregivers. Out of the total, 17 had IPTM, and at the same time, 23 had GPTM. Participating children preand post-measurements were recorded over a three-month treatment period, accessing their motor function (using the Gross Motor Functional Measure-88 (GMFM-88), Gross Motor Function Classification System Expanded & Revised version (GMFCS E&R) and Manual Ability Classification Scale (MACS)) and the caregivers' burden of care (MCSI), health-related quality of life (EQ5D 3L version of HRQoL) and satisfaction with physical therapy (MRPS). Results: Comparing outcomes between the IPTM and GTM at baseline showed no significant difference in the GMFM-88, GMFCS E&R, MACS, and VAS scores of the EQ5D 3L version of the HRQoL. However, there were significant differences between models for pre-MCSI and pre-MRPS results. There was no significant difference in intra-model comparisons of functional and caregiver outcomes, specifically, GMFCS E&R, MACS, and MCSI. However, the total dimension % of the GMFM-88 results showed a significant difference for IPTM (p = 0.004) and GPTM (p = 0.000). Similarly, there were significant differences for intra-model comparisons of VAS scores for the HRQoL (p = 0.016) and MPRS (p = 0.004) of caregivers from GPTM, whilst caregivers from IPTM had no significant difference in the VAS scores of the HRQoL (p = 0.097) and MRPS (p = 0.172). Results also showed that the GPTM had better attendance at physical therapy sessions than the IPTM.